The adoption of SMP: a technology acceptance model (TAM) perspective - Firdaus Shaari; Nur Fatin Syafiqah Salihudin; Raymond Jayasurya Jayaseelan; Muhammad Afiq Abdullah Noorazlan; Siti Nor Fadhilah Jamaluddin Yusof; Muhammad Solehin Fahmi Dzulkefli (IGI Global, 2016)
This research aims to examine the acceptability of SMP and to distinguish the adjustments which must be acquired to the system to make it worthy to users which in this case is the students. The research used a hierarchical regression for the data analysis between 220 students who stay in Universiti Malaysia Sabah Labuan International Campus (UMSLIC). Their participant is not being forced and purely voluntary. Empirical analysis via hierarchical regression confirmed that prescriptiveness, lifecycle, ease of use, usefulness and behavioural intention to adopt SMP. These empirical results give benefit for the Department of Academic Service (BPA) in UMSLIC. The department can formulate effective strategies to fulfil the demand of the student and making improvement of the system. The result of this study offer the current study towards the staff of the Department of Academic Services (BPA) that is achieved from this research is that it could help the BPA to improve and design the SMP system software.